Desenvolvimento de nanopartículas híbridas polímero lipídeo contendo cloridrato de topotecano - Silva, Emmanuelle de Jesus (2012)
Topotecan (TPT) is a water-soluble derivative of camptothecin clinically approved for treatment of ovarian cancer and lung cancer. This drug acts by inhibiting topoisomerase I, an enzyme related to nuclear DNA replication. Thus, TPT is a drug that acts in S phase of cell cycle and, therefore, requires prolonged contact with its biological target to achieve maximum effectiveness. Nanoencapsulation of TPT can prolong its contact with therapeutic target and maximize clinical efficacy. Another characteristic to highlight is that lactonic form of topotecan, active form, undergoes rapid hydrolysis pH dependent when in plasma pH, with rapid structure formation of carboxylate, which is less active. Lactonic ring may be stabilized by drug incorporation into lipid matrices, because lipid matrix provide insulation of surrounding aqueous medium. Polymer-lipid hybrid nanoparticles (PLN) are systems designed to enlarge incorporation of hydrophilic drugs into lipid matrices, as well as to extend control of drug release from such systems. In this paper, polymer-lipid hybrid nanoparticles containing topotecan were prepared by mixing the lipids stearic acid, dodecanoic acid and oleic acid using dextran sulfate as polymeric component. These PLN were compared to nanostructured lipid carriers (NLC), with same lipidic components, but obtained without polymer addition. Both, PLN and NLC were obtained by dilution technique of microemulsion and then characterized by their size, zeta potential, encapsulation efficiency, drug loading, in vitro release and drug chemical stability. Selected PLN showed drug loading of 5.48%, average diameter of 121.75 nm and polydispersity index of 0.277. Encapsulation efficiency was high (97.27%) as well as yield process (94.12%). PLN released 4.48% of drug in 24 hours, while the nanostructured lipid carriers (NLC) released five times more drug in that period (22.49%). However, release rate of PLN can be controlled by amount of ions in the medium and adding calcium chloride greatly increased release of topotecan from PLN. Both, NLC and PLN significantly increased topotecan stability when compared to free drug and PLN were superior due to possibility of controlling release and because of its greater efficiency in obtaining by dilution technique of microemulsion.